The Impact of The Star Effect and E-Marketing Strategy in Basketball Events -Taking NBA and CBA as Examples - Zhang, Ce; Huang, Yixin; Li, Liyang (Transactions on Economics, Business and Management Research, 2024)
Under the trends of digitization and globalization, the marketing strategy for basketball events has undergone rapid changes. The application of network marketing in promoting and broadcasting basketball events has become increasingly prevalent. Through literature analysis, marketing model analysis, and case analysis, this study finds that network marketing significantly impacts tournament organization and the expansion of basketball’s influence. Leveraging the star effect can help enhance influence and promote economic value improvement. Established professional leagues like the NBA have experienced the amplification effect of combining digital marketing with traditional media marketing; however, they should also be cautious not to overly rely on the star effect by considering strategic breakthroughs. Developing leagues like CBA should also focus on expanding their network marketing strategies in related fields. Through the combination of different network marketing strategies to expand the promotion of professional basketball competition in the Chinese market, to enhance the sustainable development of Chinese basketball.